The Lysosomal Sequestration of Tyrosine Kinase Inhibitors and Drug Resistance - Ruzickova, Eliska; Skoupa, Nikola; Dolezel, Petr; Smith, Dennis A; Mlejnek, Petr (Biomolecules, 2019)
The Lysosomal sequestration of weak-base anticancer drugs is one putative mechanism for resistance to chemotherapy but it has never been directly proven. We addressed the question of whether the lysosomal sequestration of tyrosine kinase inhibitors (TKIs) itself contributes to the drug resistance in vitro. Our analysis indicates that lysosomal sequestration of an anticancer drug can significantly reduce the concentration at target sites, only when it simultaneously decreases its extracellular concentration due to equilibrium, since uncharged forms of weak-base drugs freely diffuse across cellular membranes. Even though the studied TKIs, including imatinib, nilotinib, and dasatinib, were extensively accumulated in the lysosomes of cancer cells, their sequestration was insufficient to substantially reduce the extracellular drug concentration. Lysosomal accumulation of TKIs also failed to affect the Bcr-Abl signaling. Cell pre-treatment with sunitinib significantly enhanced the lysosomal accumulation of the TKIs used; however, without apparent lysosomal biogenesis. Importantly, even increased lysosomal sequestration of TKIs neither decreased their extracellular concentrations nor affected the sensitivity of Bcr-Abl to TKIs. In conclusion, our results clearly show that the lysosomal sequestration of TKIs failed to change their concentrations at target sites, and thus, can hardly contribute to drug resistance in vitro.
Keywords: extracelulární prostor; extralysosomal space; Extracellular Space; buňky K562; inhibitory proteinkinas; lysosomal sequestration; lyzozomy; Humans; K562 Cells; Sunitinib; extracellular space; tyrosinkinasy; drug resistance; tyrosine kinase inhibitors; Drug Resistance, Neoplasm; lidé; target sites; chemorezistence; sunitinib; Protein Kinase Inhibitors; Lysosomes; Protein-Tyrosine Kinases